Bond Ability of Oil Palm Xylem with Isocyanate Adhesive - Atmawi Darwis; Muhammad Y Massijaya; Naresworo Nugroho; Eka M Alamsyah; Dodik R Nurrochmat (Jurnal Ilmu dan Teknologi Kayu Tropis, 2014)
Oil palm xylem composed of vascular bundles and parenchyma tissue and directly related to its properties. Utilization of oil palm xylem into the wood laminate products requires information on its bond ability to adhesive used. Isocyanate adhesive is a prospective adhesive due to its various advantages compared to other adhesives. This study aimed to obtain information about the bond ability of the oil palm xylem with isocyanate adhesive. The results showed that isocyanate adhesive has good wettability on oil palm xylem indicated by its contact angle of below 90°. Isocyanate adhesive also showed good performance by looking at the value of wood failure and delamination. However, the shear strength of laminated oil palm xylem was low. Wood failure occurred in the parenchymal tissues region.Key words: bond ability, isocyanates, laminated board, oil palm xylem